SARS-CoV2 Outbreak: Emergence, transmission and clinical features of human coronaviruses - Imran, Muhammad; Yasmeen, Rehana (Journal of Ayub Medical College Abbottabad, 2021)
The novel coronavirus was emerged from China Wuhan city and spread around the globe within a few days. COVID-19 is rapidly transmitted from one human to another, and it is also a highly pathogenic infection. Genetic analysis confirmed that SARS-CoV 2 is phenotypically related to SARS-CoV; therefore, the possible reservoir for SARS-CoV 2 could be bats. According to WHO more than 20 million individuals infected with SARS-CoV 2 while more than 700,000 peoples lost their lives due to COVID-19 as of 13th August 2020. Up-till now, there is no anti-viral therapy or vaccines available for the treatment and prevention of COVID-19. Although dexamethasone and tocilizumab help in reducing mortality among critical patient infected with COVID-19 However, China, Brazil and USA have developed vaccines which is currently under trial phase. Still, up-till now, there is no clinically approved treatment regimen available against COVID-19. Keywords: Human Coronavirus; SARS-CoV 2; Transmission of COVID-19; Treatment of coronavirus; Vaccine